INDUCTION OF MUTATION THROUGH GAMMA IRRADIATION IN NON-BASMATI AROMATIC ‘BADSHABHOG’ RICE (Oryza sativa L.) (Applied Biological Research, 2023)
Induction of several types chlorophyll and viable morphological mutations  were studied in M2 generation of non-basmati aromatic Badshabhog rice  in all five different doses (200, 250, 300, 350 and 400 Gy) of gamma rays.  Chlorophyll frequency was increased with increasing dose of gamma rays.  Among different chlorophyll mutations albino was the most frequent type.  Several morphological mutants such as short-stature, early maturity,  increased tillering, dark green broad leaf, narrow leaf, short exerted  panicle, complete spikelet sterility, double-triple spikelet, double kernel  within spikelet and lodging resistant type were appeared with variable frequencies by different doses of gamma rays in 2,07,960 individual  plantlets from M2 population. Among them short-stature mutant was  predominate type. A nonlinear relationship was noticed between dose of  gamma rays and frequency of viable mutations. The mutagenic efficiencies  were increased with increase in irradiation dose but no relationship  between the doses of mutagen and mutagenic effectiveness was established.  Less damages in biological traits such as lethality, injury and sterility were  observed at 200 to 300 Gy dose of gamma rays. Desirable mutants were  found at 200 and 300 Gy.
Keywords: Badshabhog rice; chlorophyll; gamma-irradiation; mutants